2018
DOI: 10.14202/vetworld.2018.824-829
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activity of Acanthaster planci phospholipase A2 against human immunodeficiency virus

Abstract: Aim:Investigation of antiviral activity of Acanthaster planci phospholipase A2 (AP-PLA2) from moluccas to human immunodeficiency virus (HIV).Materials and Methods:Crude venom (CV) and F20 (PLA2 with 20% fractioned by ammonium sulfate) as a sample of PLA 2 obtained from A. planci’s extract were used. Enzymatic activity of PLA2 was determined using the degradation of phosphatidylcholine (PC). Activity test was performed using in vitro method using coculture of phytohemagglutinin-stimulated peripheral blood monon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…The finding of this research supports the hypothesis of PLA2 from animal venom which exhibits antiviral activity that may inhibit HIV replication by several other researchers [8,10,26]. Our results are similar to Fenard et al .…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The finding of this research supports the hypothesis of PLA2 from animal venom which exhibits antiviral activity that may inhibit HIV replication by several other researchers [8,10,26]. Our results are similar to Fenard et al .…”
Section: Resultssupporting
confidence: 93%
“…This is a lower value than the LC 50 of PLA2 from A. planci venom obtained by Wijanarko et al . which was 1.64 mg/ml [10].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Real Time-qPCR and gel electrophoresis revealed that the expression of the HIV group-specific antigen (Gag) strongly decreased in treated PBMC cells. The decline of infection rates was also confirmed by immunofluorescence approaches [190].…”
Section: Echinodermsmentioning
confidence: 68%
“…PV-PLA2 has been shown to affect antiretroviral activity of SRV2, suggesting that PV-PLA2 can be a good anti-HIV drug candidate [251]. PLA2 from other source has been also found to have antiretroviral activity against HIV [190,252,253].…”
Section: Marine Vertebratesmentioning
confidence: 99%